Perceptions of livestock value chain actors (VCAs) on the risk of acquiring zoonotic diseases from their livestock in the central dry zone of Myanmar - Tu Tu Zaw Win; Angus Campbell; Ricardo J. Soares Magalhaes; Kyaw Naing Oo; Joerg Henning (BMC, 2023)
Abstract Objectives The Central Dry Zone (CDZ) is one of the most important livestock production areas of Myanmar. However, there is an eminent lack of information on the attitudes and traditional beliefs of local farmers and livestock supply chain actors in CDZ of Myanmar on the public health implications. A modified data collection instrument of the Health Belief model was developed to investigate attitudes, beliefs and barriers to the application of recommended zoonotic disease prevention. Study design Cross-sectional study. Method Data analyses were conducted considering a two-phase multilevel mixed effect binomial generalized linear models modelling approach. Results The availability of information about zoonosis to supply chain actors influenced their confidence to implement preventive actions (OR = 1.5, p = 0.045 for cattle diseases; OR = 1.5, p = 0.022 for village chicken diseases). Supply chain actors were more likely aware of zoonosis transmitted by cattle compared to livestock farmers (OR = 0.3, p = 0.005 for cattle farmers), while people not rearing or trading small ruminants and/or poultry were less likely to be aware of the zoonotic risk associated with these animals (p < 0.005). Information on zoonosis transmitted from small ruminants was mainly promoted through farmers (p = 0.032), while information on zoonotic diseases that can be obtained from chickens was disseminated through farmers, local authorities and the media. Nevertheless, appropriate hand hygiene measures (i.e. cleaning of hands after touching, cutting, cooking meat) (OR = 7.7, p < 0.001 for zoonotic small ruminant diseases; OR = 1.6, p = 0.073 for zoonotic village chicken diseases) and treating of sick animals (OR = 7.3, p < 0.001 for small ruminant zoonotic diseases; OR = 2.2, p = 0.031 for village chicken zoonotic diseases) increased the confidence of small ruminant and village chicken owners to prevent these zoonotic infections. Conclusions The findings from this study indicate that while gender and the availability of information on zoonotic risks play an important role on the perceived threat of zoonoses, the practice of prevention methods influenced the confidence of value chain actors (VCAs) on zoonoses prevention.